2014
DOI: 10.1002/jhrm.21131
|View full text |Cite
|
Sign up to set email alerts
|

Improved obstetric safety through programmatic collaboration

Abstract: Healthcare safety and quality are critically important issues in obstetrics, and society, healthcare providers, patients and insurers share a common goal of working toward safer practice, and are continuously seeking strategies to facilitate improvements. To this end, 4 New York City voluntary hospitals with large maternity services initiated a unique collaborative quality improvement program. It was facilitated by their common risk management advisors, FOJP Service Corporation, and their professional liabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…16,17 Furthermore, Crofts et al 12 showed that multiprofessional simulation-based obstetric training improved perceived quality of care, although this was reported by patient-actors instead of real patients. Previous research showed that multidisciplinary team training in crew resource management (CRM) results in positive reactions among trainees.…”
mentioning
confidence: 97%
“…16,17 Furthermore, Crofts et al 12 showed that multiprofessional simulation-based obstetric training improved perceived quality of care, although this was reported by patient-actors instead of real patients. Previous research showed that multidisciplinary team training in crew resource management (CRM) results in positive reactions among trainees.…”
mentioning
confidence: 97%
“…Other studies have examined the impact of CTG education on neonatal outcomes, most of them in the context of other interventions and most finding no effect on low pH values or Apgar score . The implementation of the Fetal Surveillance Education Program in Australia was associated with a decrease in incidence of hypoxic ischemic encephalopathy .…”
Section: Discussionmentioning
confidence: 99%
“…Standardized protocols have been shown to decrease medical errors, iatrogenic injury and improve patient outcomes across a broad range of medical specialties (13–15). All of the patients in our study were cared for by an experienced team of nurses, operating room technicians and physicians who used a standardized approach to patient positioning.…”
Section: Discussionmentioning
confidence: 99%